Evaluation of adsorption mechanism of mercury using mangosteen via elemental distribution and binding energy analyses - Fumihiko Ogata (2020)
© 2020 Elsevier Ltd In this study, the application of mangosteen pericarp (MG) as a bio-sorbent based on agricultural waste was assessed for the removal of Hg(II) from aqueous media. The MG was calcined at 500 °C and 1000 °C and was denoted as MG500 and MG1000, respectively. Physicochemical properties were investigated, and the adsorption capability on Hg(II) was assessed. Additionally, the adsorption mechanism on Hg(II) from aqueous media was evaluated via elemental distribution and binding energy analyses. It was observed that the adsorption capability on Hg(II) using MG500 was greater than that of the Hg(II) using MG and MG1000. Additionally, the optimal pH for the removal of Hg(II) from aqueous media using MG500 was approximately 5.0. The intensity of Hg(II) increased after adsorption, and the binding energies of Hg(II) were detected at approximately 100 eV. This result aids in the elucidation of one of the adsorption mechanisms on Hg(II) using MG500.